The Antioxidant Properties, Metabolism, Application and Mechanism of Ferulic Acid in Medicine, Food, Cosmetics, Livestock and Poultry - Mengli Zheng; Yating Liu; Guanfeng Zhang; Zhikang Yang; Weiwei Xu; Qinghua Chen (MDPI AG, 2024)
Ferulic acid is a ubiquitous ingredient in cereals, vegetables, fruits and Chinese herbal medicines. Due to the ferulic phenolic nucleus coupled to an extended side chain, it readily forms a resonant-stable phenoxy radical, which explains its potent antioxidant potential. In addition, it also plays an important role in anti-cancer, pro-angiogenesis, anti-thrombosis, neuroprotection, food preservation, anti-aging, and improving the antioxidant performance of livestock and poultry. This review provides a comprehensive summary of the structure, mechanism of antioxidation, application status, molecular mechanism of pharmacological activity, existing problems, and application prospects of ferulic acid and its derivatives. The aim is to establish a theoretical foundation for the utilization of ferulic acid in medicine, food, cosmetics, livestock, and poultry.